Contributions of Rural Non-Farm Economic Activities to Household Income in Lere Area, Kaduna State of Nigeria - J. U, Madaki; Adefila, J. O (International Journal of Asian Social Science, 2014)
It is obvious that agricultural productivity is low in the developing countries and it often leads to low income which demands for diversifying economic activities as a strategy to meet numerous needs of the households. In the rural communities, most households engaged in non-farm activities in order to boost economic base. This study examined the contributions of non-farm activities to the employment generation and total income of rural households in Lere Local Government area of Kaduna State, Nigeria. The study drew a sample of 382 rural households through a multi-stage sampling technique and the data obtained through questionnaire survey were analyzed using the descriptive statistics and analysis of means techniques. The results indicated that there was an increase of about (4.0%) in employment generation within the non-farm sector of the rural economy between 2007 and 2011. The household income from farm and non-farm was compared and it was discovered that (44.8 %) of the total income was associated with households that ventured into farming only and (55.2%) accounted for households that engaged in non-farm activities. The student t-test revealed that calculated value (3.88) and critical value (1.96) showing a significant difference at 0.05 alpha value between household incomes from farm and non-farm economic activities during the same period. On the basis of the findings, the study recommended that government should give more recognition to non-farm economic activities in rural areas by designing policies that will equip poor households with better skills, increased investment in infrastructure, and accessibility to financial resources.